PENANAMAN NILAI-NILAI PENDIDIKAN MULTIKULTURAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM 2013 DI SMP BUSTANUL MAKMUR GENTENG BANYUWANGI - Nasrodin Nasrodin; Eka Ramiati (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
This study aims to describe and analyze the implementation of multicultural educational values consisting of democratic, humanist and pluralist values in the 2013 curriculum in Islamic religious education subjects at Bustanul Makmur Genteng Banyuwangi Junior High School. It is a qualitative research with a phenomenological approach. Data collection techniques include: observation, interviews and documentation. Data analysis includes: data collection, Condensation Data, display data, and drawing conclusions or verification. The validity of the data is tested by source triangulation and method triangulation. The results of this study show that: (1) The implementation of Democratic values in the 2013 curriculum in Islamic religious education subjects for Students of Bustanul Makmur Junior High School is carried out through the first student organization, namely by the election of the Chairman of the Student Council, and the election of the class leader, the second is the preparation of school rules by deliberation, the third is the learning process of Islamic religious education, the fourth is to provide freedom of expression and expression of opinions. (2) The implementation of Humanist values in the 2013 curriculum in islamic religious education subjects of Bustanul Makmur Junior High School students is carried out through firstly Teaching social care through Friday Charity, secondly with a service program through home stay activities, thirdly holding Clean Saturday activities, fourth holding social service activities including: compensation for orphans, helping underprivileged residents, and residents affected by disasters, fifth through the learning process of Islamic religious education, namely teachers providing understanding to students. (3) The implementation of Pluralist values in the 2013 curriculum in islamic religious education subjects for students of Bustanul Makmur Genteng Banyuwangi Junior High School is carried out through the first way by involving all students in all student and religious activities without discriminating between students, the two teachers become tauladan / examples for students, thirdly through the learning process of Islamic religious education.